Histological Analysis of Changes in Brain Tissues of Rats with Experimental Parkinson Disease Prior to and After Transplantation of Cryopreserved Embryonic Nerve Cells - Pyatikop, V. A.; Karamyshev, V. D.; Shevereva, V. M.; Dvortsevoy, V. K. (Problems of Cryobiology and Cryomedicine, 2006)
There are presented histomorphological characteristics of cryopreserved embryonic nerve cells (ENCs) transplants in rats with experimental parkinsonism, induced by bilateral anode electrolysis of substantia nigra. Engrafted ENCs were shown to proliferate within the introduction area and beyond the scar. The introduced neuroblasts are spread beyond the proliferation area as well.